Quantity judgment and the mass-count distinction across languages: Advances, problems, and future directions for research. Issue 1 (18th May 2018) - Bale, Alan; Barner, David
Abstract : We review advances in the experimental study of the mass-count distinction and highlight problems that have emerged. First, we lay out what we see to be the scientific enterprise of studying the syntax and semantics of the mass-count distinction, and the assumptions we believe must be made if additional progress is to occur, especially as the empirical facts continue to grow in number and complexity. Second, we discuss the new landscape of cross-linguistic results that has been created by widespread use of the quantity judgment task, and what these results tell us about the nature of the mass-count distinction. Finally, we discuss the relationship between the mass-count distinction and non-linguistic cognition, and in particular the object-substance distinction.